2017
DOI: 10.1111/jon.12474
|View full text |Cite
|
Sign up to set email alerts
|

Seven‐Tesla Magnetization Transfer Imaging to Detect Multiple Sclerosis White Matter Lesions

Abstract: BACKGROUND AND PURPOSE: Fluid-attenuated inversion recovery (FLAIR) imaging at 3 Tesla (T) field strength is the most sensitive modality for detecting white matter lesions in multiple sclerosis. While 7T FLAIR is effective in detecting cortical lesions, it has not been fully optimized for visualization of white matter lesions and thus has not been used for delineating lesions in quantitative magnetic resonance imaging (MRI) studies of the normal appearing white matter in multiple sclerosis. Therefore, we aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Second, lesion detection was performed using MT sat (MTR based on proton- and T2*-weighted imaging with presaturation to water) images, which might not be as accurate as 3T fluid-attenuated inversion recovery (FLAIR) images. However, we previously showed that 7T-MT sat sequences detected most of the WM lesions identified by 3T-FLAIR sequences, and missed only approximately 1.5% of small lesions 34 ; hence, patients do not need to undergo both 7T and 3T scans on the same day. Third, the temporal lobes were not all included because the signal loss caused by inhomogeneity in the applied transmit radiofrequency (RF) field at high field strength was more pronounced in these regions.…”
Section: Discussionmentioning
confidence: 97%
“…Second, lesion detection was performed using MT sat (MTR based on proton- and T2*-weighted imaging with presaturation to water) images, which might not be as accurate as 3T fluid-attenuated inversion recovery (FLAIR) images. However, we previously showed that 7T-MT sat sequences detected most of the WM lesions identified by 3T-FLAIR sequences, and missed only approximately 1.5% of small lesions 34 ; hence, patients do not need to undergo both 7T and 3T scans on the same day. Third, the temporal lobes were not all included because the signal loss caused by inhomogeneity in the applied transmit radiofrequency (RF) field at high field strength was more pronounced in these regions.…”
Section: Discussionmentioning
confidence: 97%
“…The latter protons do not directly contribute to the observed MRI signal in conventional sequences because of their short transverse relaxation times. The MT ratio (MTR) is a semi‐quantitative measure of the MT effect that can be estimated from an MT‐weighted and reference image . Studies indicate that MTRs change with myelin and axonal content, indicative of the degree of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The MT ratio (MTR) is a semiquantitative measure of the MT effect that can be estimated from an MT-weighted and reference image. 10,11 Studies indicate that MTRs change with myelin and axonal content, 12,13 indicative of the degree of neurodegeneration. In addition, MTR is sensitive to inflammation and edema.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of 7-T MRI for detecting MS white matter lesions is less robust than that for the cortex [ 43 ] with ongoing research in the optimization of sequences to reduce limitations secondary to high SAR and to reduce RF field inhomogeneities [ 43 45 ]. T2*, FLAIR, magnetization transfer imaging, and magnetization-prepared rapid gradient-echo have been suggested as currently recommended sequences to visualize white matter lesions at 7 T [ 43 , 46 , 47 ].…”
Section: Ultrahigh Field Mrimentioning
confidence: 99%